Implementasi Metode Bercerita Mengembangkan Karakter Anak Usia Dini Di Taman Kanak-Kanak Negeri Pembina Lut Tawar Takengon - Cibro, Juniara Fitri; Fitri, Junita (EL-Hadhary: Jurnal Penelitian Pendidikan Multidisiplin, 2024)
ABSTRACT The background to the research problem at the Pembina Lut Tawar State Kindergarten is that the storytelling method used by teachers is still not optimal when developing the character of early childhood. There are still some children whose character has not developed well. When studying, some children still don't understand themselves. They still have to listen to instructions from the teacher and still whisper while implementing the storytelling method. The aim of this research is to see the character development and reactions of children after the implementation of the storytelling method and what impacts/characters emerge in children after the storytelling method is implemented. The research method used to see the implementation of the storytelling method to see the development of children's character uses Classroom Action Research (PTK) which is carried out collaboratively between researchers and class teachers. The results of the research showed that the pre-cycle percentage based on observations of the average child score was 26%. During the implementation of Action I (Cycle 1) the average percentage of children's scores was 48%. In the implementation of Action II (Cycle 2) the average percentage of children's scores was 75%. So, the implementation of the storytelling method in developing the character of early childhood has increased by 27%. Then, from this increase we can see the development of children's character, namely religious, honest, disciplined, independent, creative, responsible, caring, able to work together, tolerant, critical. Keywords: Implementation, Storytelling Method, Characters